Government board of director: the influence of director identifications on human capital acquisition and board oversight roles - Sharifah Azlina Syed Anuar,; Noradiva Hamzah,; Mohd Mohid Rahmat, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Identification is a sense of belonging to particular social groups with similar characteristics or similarly perceived role identities. The strength of an individual's identification is context-dependent and can influence an individual’s behavior according to certain expectations. Despite abundant research on board oversight roles, little is known about why board members behave in certain ways due to a lack of literature from a socio-behavioral perspective. This paper explores how identification with social groups and role identities among the government board of directors (GBOD) influence their human capital and board roles. The results, derived from semistructured interviews of twelve government officials who were appointed to the boards of Malaysian State-Owned Enterprises (SOEs) as government representatives, indicate that different identifications, such as the role of government board of director, corporate director, or both, and identification with the SOE could lead to different perceptions of the importance of human capital and influence their contributions in boardrooms. This study provides empirical evidence for the corporate governance literature from a socio-behavioral perspective and helps government agencies and regulators understand the reasons behind GBOD behavior. Selecting board members based on their human capital may be inadequate, and board members may need training to help them identify their roles and responsibilities as government representatives on the board